Empire of influence: the East India Company and the making of indirect rule - Wilkinson, Callie 1990- (Cambridge, UK; New York, USA: Cambridge University Press, 2023)
"This book makes important contributions to the history of the East India Company and the history of indirect rule. It will be relevant for students and academics interested in India, the British empire, and European overseas empires generally"--
A Time of Trouble -- Negotiating the Disinformation Order -- Warfare and 'Wanton Provocations' -- The Price of Pageantry -- Weak Ties in a Tangled Web -- Kinship, Gender, and Dynastic Dramas.
Includes bibliographical references and index.
Keywords: East India Company -- History -- 19th century; British -- India -- History -- 19th century; India - History; Postcolonial; Great Britain -- Colonies -- Asia -- Administration; India -- Politics and government -- 19th century; India -- Kings and rulers -- History -- 19th century